Physico-Chemical Characterisation Of Mangrove Tannins As Corrosion Inhibitors - Rahim, Afidah Abdul (2005)
Tannins from mangrove barks have been successfully extracted using 70 % aqueous acetone and purification by LH-20 column chromatography afforded condensed tannins of high purity.